Oil Types of the Norwest Basin of Argentina - Ale Ruiz, Elisa Liliana (2018)
Prior to producing a hydrocarbon deposit, performing a PVTstudy is necessary so that, based on the results of the studies, thevarious parameters and methodologies that will be developed toproduce the deposit are determined. The PVT study is absolutelynecessary in order to design the production facilities; in parallel,with this information the POES (Original Petroleum In Site) of theoilfield, the productive life of the deposit and the optimal productionschemes are determined, in addition to evaluate methods ofimproved recovery of hydrocarbons and others properties thatpredict the behavior of the wells as they are exploited.One part of the PVT study, the compositional one, is ofgreat importance in the engineering of oilfields, since it helpsto characterize the oilfield type and the volumetric conditionsin which the oil is found, through the analysis of its behavior(volumetric and compositional), in order to establish the beststrategy of exploitation and separation on the surface. This studyinvolves a set of laboratory analysis of the samples, one of whichis the differential expansion of the fluid sample to determine theBo (volumetric factor of oil formation) and RPG or GOR (gas-oilrelationship), this last ones are essential to classify oil in situ, inaddition to the API gravity.